Investigation of gastric function and prevalence of Helicobacter pylori in non-ulcer dyspepsia - Takayasu, H; Harasawa, S; Miwa, T; Yamada, Y (Nippon Shōkakibyō Gakkai zasshi, 1993)
One hundred and fourty four patients with non-ulcer dyspepsia (NUD), as defined by the working party of AGA in 1987, (67 men and 77 women, 16-76 years, mean age 42.9 +/- 1.2 years) and 34 asymptomatic controls (25 men and 9 women, 17-75 years, mean age 50.6 +/- 2.4 years) parameters of gastrophysiological function (gastric acid secretion, postprandial gastric emptying-acetaminophen method, serum gastrin levels and cutaneous electrogastrography (EGG)) and the prevalence of Helicobacter pylori (Hp) (histological and urease test of biopsy specimens) were investigated. Based on symptom patterns, there were 68 patients with dysmotility-like dyspepsia, 27 with ulcer-like dyspepsia, 17 with reflux-like dyspepsia, 6 with aerophagia and the 26 with nonspecific or idiopathic dyspepsia. The age distribution of NUD was predominant in the fourth decade, and the sex distribution was not significantly different. In general, hypersecretion of gastric acid and hypergastrinemia were rare in NUD patients. There was no significant difference in gastric acid secretion, basal and food stimulated serum gastrin levels and prevalence of Hp between the two groups. But 51 of 144 NUD patients (41.1%) had delayed gastric emptying (p < 0.05) compared to controls. Indeed gastric emptying was markedly prolonged in patients with dysmotility-like (58.1%) and reflux-like (42.9%) dyspepsia. On EGG, about a half of NUD patients showed evidence of bradygastria or tachygastria, in particular in the postprandial state, which was related to delayed gastric emptying. By chronic administration of cisapride, score of symptoms was significantly decreased and postprandial gastric emptying was significantly accelerated in delayed gastric emptying cases. We conclude that in NUD patients, in particular those with dysmotility-like dyspepsia, tests of postprandial gastric emptying and/or EGG are useful for investigation of gastric motor disorder and therapeutic effects of several prokinetic drugs clinically.